Tourist Behavior Regarding Smoking in Tourist Areas in Medan City - Sembiring Marwiyah Ikhwanil; Siregar Apriadi Putra; Ritonga Aidah Asnil; Aidha Zuhrina; Ayu Delfriana (Journal of Innovative and Creativity, 2025)
The study purpose was … This study aims to analyze tourists’ smoking behavior in Medan City’s tourist areas by focusing on attitudes, subjective norms, intentions, and actual behaviors. Materials and methods. A quantitative survey was conducted with 75 tourists in five popular destinations of Medan City. Data were collected through validated and reliable questionnaires, then analyzed using normality tests, univariate, and bivariate analysis with chi-square. Results. The results showed that most tourists had permissive attitudes toward smoking, although a few were aware of its negative impacts. Subjective norms from peers and the social environment strongly influenced tourists’ intentions to smoke. This intention eventually turned into actual behavior, with 72% of respondents smoking in tourist areas. The implementation of the Smoke-Free Area (SFA) policy was found ineffective since 82% of respondents admitted they had never seen monitoring on site. Conclussion. These findings confirm that tourists’ smoking behavior is a complex interaction between personal and social factors. Therefore, tourism management strategies should focus on enforcing SFA regulations, providing designated smoking areas, and conducting community-based health education.